The Effect of Inorganic Fertilizer and Liquid Organic Fertilizer on Growth and Yield Curly Red Chili Plants (Capsicum annuum - Yuliani (Indoensia), Norama; Farid (Indoensia), Noor; Laeshita (Indoensia), Putri (JURNAL VIGOR, 2024)
Red chili production in Indonesia has decreased, one of the efforts to increase red chili production is through fertilization techniques. Research on the effect of inorganic fertilizers and liquid organic fertilizers on the growth and yield of red curly chili plants (Capsicum annuum L.) was carried out in August-December 2022 in the experimental field of Tamping Winarno Village, Sukorejo District, Kendal Regency. The aim of the study was to determine the effect of giving inorganic and liquid organic fertilizer concentrations and their combinations on the growth and yield of curly red chili (Capsicum annuum L.). The research method used was arranged in a completely randomized block design (RCBD) with 2 factorial. The first treatment was : concentration of liquid organic fertilizer (N0 = 0 ml, N1 = 10 ml, N2 = 20 ml). The second treatment was: concentration of AB mix fertilizer (P1=1 ppm, P2 = 2 ppm, P3 = 3 ppm). The results of the analysis showed that the concentration of liquid organic fertilizer of 10 ml gave optimal results for plant height parameters. Concentration of inorganic fertilizer (AB mix) 2 ppm gave optimal results on the number of branches parameter. The parameters of the number of fruit planted, the weight of the fruit planted, the weight of fresh stover, and the harvest index did’t significantly affect the treatment of liquid organic fertilizer and inorganic fertilizer (AB mix).